Genotyping and phylogenetic analysis of free-living amoeba (Acanthamoeba and Naegleria) in treated and untreated water in the northeastern provinces of Iran. Issue 3 (20th December 2021) - Sharifi, Yousef; Ahmadi, Omid; Hossini Farash, Bibi Razieh; Khosravinia, Nazgol; Fotouhi-Ardakani, Reza; Moghaddas, Elham; Berenji, Fariba; Baradaran, Ashkan; Poursheikhani, Arash; Mirjalali, Hamed; Zarean, Mehdi
Abstract: Free-living amoebae (FLA) are widely distributed protozoa in natural or man-made aquatic environments without the need for a host organism for survival. Several strains of FLA are known to be pathogenic. As of date, there is inadequate data on the geographical distribution of FLA in northeastern and northern Iran. This study aimed to investigate the prevalence and genotype distribution of Acanthamoeba and Naegleria in drinking water and surface water samples in northern and northeastern Iran. A total of 60 water samples were collected and filtered from various sources for the presence of amoebae. DNA extraction was performed, and PCR confirmed the presence of FLA. PCR products were sequenced to identify the species/genotype. Phylogenetic relationships and taxonomic status constructed using MEGA X software. The findings on growth media showed 35% (21/60) and 26% (16/60) were positive for Acanthamoeba and Naegleria, respectively, while PCR analysis also obtained similar results. All isolates of Acanthamoeba were identified as T4 genotype. Poor water quality, as well as insufficient preservation and treatment, might indicate that chlorine disinfection is ineffective in removing contamination of amoebas in treated water samples. Therefore, regular water quality monitoring is essential to control amoeba's growth, reducing the risk of human infections with FLA. HIGHLIGHTS: The presence of FLA was evaluated in treated/untreated drinking water. Acanthamoeba sp., and Naegleria spp., were identified among 21 (35%) and 16 (26%) of samples. All Acanthamoeba isolates were T4 genotypes. Naegleria spp., were N . americana, N . dobsoni, N . pagei, and N . australiensis .